Clonality in haematopoietic stem cell ageing. (July 2020) - Terradas-Terradas, Maria; Robertson, Neil A.; Chandra, Tamir; Kirschner, Kristina
Highlights: Somatic driver mutations lead to clonal haematopoiesis of indeterminate potential (CHIP) in aged haematopoietic stem cells. CHIP is associated with a variety of age-related multimorbidities. How environmental and cell-intrinsic factors contribute to CHIP and development of multimorbidities is poorly understood. Increased inflammatory signalling with age might be one mechanism driving age-related disease and favouring outgrowth of HSCs carrying specific driver mutations. Abstract: Clonal haematopoiesis of indeterminate potential (CHIP) is widespread in the elderly. CHIP is driven by somatic mutations in leukaemia driver genes, such as Janus Kinase 2 ( JAK2 ), Tet methylcytosine dioxygenase 2 ( TET2 ), ASXL Transcriptional Regulator 1 ( ASXL1 ) and DNA (cytosine-5)-methyltransferase 3A ( DNMT3A ), leading to reduced diversity of the blood pool. CHIP carries an increased risk for leukaemia and cardiovascular disease. Apart from mutations driving CHIP, environmental factors such as chemokines and cytokines have been implicated in age-dependent multimorbidities associated with CHIP. However, the mechanism of CHIP onset and the relationship with environmental and cell-intrinsic factors remain poorly understood. Here we contrast cell-intrinsic and environmental factors involved in CHIP development and disease propagation.